Incidence and predictors of mortality in children with diabetic ketoacidosis in the comprehensive specialized referral hospitals of West Amhara Region, Northwest Ethiopia: a retrospective follow-up study - Shimelash, Rahel Asres; Belay, Getaneh Mulualem; Aknaw, Worknesh; Shibabaw, Aster Tadesse; Adebabay, Aderajew Agmas; Gedefaw, Gezahagn Demsu; Kassie, Tadele Derbew; Zemariam, Alemu Birara (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: Diabetic ketoacidosis is one of the major life-threatening condition of acute metabolic complications. It remains a major public health problem in developing countries including Ethiopia. Objective: To assess incidence and predictive of mortality among children with diabetic ketoacidosis in West Amhara region Comprehensive Specialized Referral Hospitals, North West Ethiopia, 2022. Methods: An institution-based retrospective follow-up study was conducted among 423 study participants with confirmed diagnosis of diabetic ketoacidosis from January 1 st , 2017 to December 31 th , 2021. Data was entered, coded, cleaned, and checked by Epi-Data version 4.6 and exported to Stata version 14 for data analysis.Result: A total of 401 children records were included in the final analysis and observed for 3781 days throughout study period. The overall mortality of children with diabetic ketoacidosis was 10.6 per 1000 person-days observation (95 % CI: 7.8-14.4) during the entire follow-up period. Hypoglycemia (AHR=4.6; 95 % CI: 2.13-10.1), rural residency (AHR=2.9; 95 % CI=1.01-8.11), age less than five years (AHR=4.4; 95 % CI=1.4-13.7), age five up to ten (AHR=3.1; 95 % CI=1.1-8.8) and female sex (AHR=2.6; 95 % CI=1.1-5.8) were significant predictive.Incidence rate of mortality among children with diabetic ketoacidosis was relatively high. Age, rural residency, female sex, and hypoglycemia were significant predictive of mortality. Community education or mass campaign about signs and symptoms of diabetic ketoacidosis may decrease death rate of children.